An improved quartic B-spline based explicit time integration algorithm for structural dynamics - Wen, Weibin; Deng, Shanyao; Liu, Tianhao; Duan, Shengyu; Huang, Fanglin (European journal of mechanics, A, Solids, 2022)
In this study, an improved explicit time integration method based on quartic B-spline interpolation is generalized for linear and nonlinear dynamics. The accuracy order of the proposed method is analytically obtained as well as its spectral radius, period elongation, and algorithmic damping. The analysis shows the proposed method achieves third-order and at least second-order accuracy for displacement and velocity, respectively. With one algorithmic parameter, the proposed method can adjust numerical dissipation and accuracy. Linear dynamic examples demonstrate that the effectiveness of the proposed method as well as its high-order accuracy. Nonlinear dynamic problems show the proposed method can provide desirable solutions. Numerical results demonstrate the proposed method can provide more stable and accurate solutions than other classical explicit methods. •An improved simple explicit time integration method based on quartic b-spline interpolation is proposed.•New method can achieve third-order accuracy with desirable numerical dissipation.•High accuracy and robustness of the proposed method for both linear and nonlinear problems.